Comportamento ingestivo de bovinos mantidos em pastos de Brachiaria brizantha cv. Xaraés manejado em diferentes alturas de pastejo - Alves de Freitas Barbosa, Marco Aurelio; Castro, Leticia Maria; Barbero, Rondineli Pavezzi [UNESP]; Brito, Vinicius Campachi; Miorin, Renan Lucas; Saad, Rafael Mantegazza; Azambuja Ribeiro, Edson Luis de; Bumbieris Junior, Valter Harry (Univ Estadual Londrina, 2013)
This experiment was conducted to evaluate the effect of grazing heights on daytime behavioral activities of Nellore beef cattle in the rainy season. The experimental area was 12 hectares divided into paddocks of one hectare each. The treatments consisted of four defoliation heights (15, 30, 45 and 60 cm) in pastures of Brachiaria brizantha cv. Xaraes with three replicates each. It was used the continuos grazing method, with variable stocking rate. Forage samples collected on the plots were sent to the laboratory for separation of the botanical components, weighing and determination of dry matter, with the material collected by simulated grazing. The variables: grazing time, idle time and ruminating time were evaluated for 12 consecutive hours on days 15 and 16 February 2011, considering the morning and afternoon periods. It was used a completely randomized design. The height of the canopy significantly influenced the daily grazing time and ruminating time, with a quadratic response as a function of time of defoliation. The bite rate decreased as a function of heights studied. However the chemical composition of the material collected by simulated grazing did not differ between treatments. Xaraes grass swards grazed at around 45 cm height provide greater ease of apprehension by grazing cattle.
Ingestive behavior of cattle kept in Brachiaria brizantha cv. Xaraes grass managed under different grazing heights
Keywords: Bit rate; idleness; rumination; simulation of grazing